2008
DOI: 10.1590/s1413-86702008000100017
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia in an adult clinical-surgical intensive care unit of a Brazilian university hospital: incidence, risk factors, etiology, and antibiotic resistance

Abstract: The objective of this study was to evaluate clinical characteristics, etiology, and resistance to antimicrobial agents, among patients with ventilator-associated pneumonia (VAP). A case study vs. patients control under mechanical ventilation and hospitalized into clinical-surgical adults ICU of HC-UFU was performed from March/2005 to March/2006. Patients under ventilation for over 48 h were included in the study including 84 with diagnosis of VAP, and 191 without VAP (control group). Laboratory diagnosis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
5
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 38 publications
5
36
5
10
Order By: Relevance
“…Although many studies have shown tracheotomy to be a major risk factor for VAP development [13][14][15][16][17][18][19] , our study results do not support that claim. Our data suggest that lower VAP incidences are to be expected in tracheotomized patients.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…Although many studies have shown tracheotomy to be a major risk factor for VAP development [13][14][15][16][17][18][19] , our study results do not support that claim. Our data suggest that lower VAP incidences are to be expected in tracheotomized patients.…”
Section: Resultscontrasting
confidence: 98%
“…The impact of tracheotomy on the development of VAP is not clearly defined. Some studies found decreases in VAP rates in patients having tracheotomy [6][7][8][9][10][11][12] , others have reported tracheotomy to be a risk factor favoring VAP onset [13][14][15][16][17][18][19][20] , while some could not demonstrate any VAP-related impact whatsoever [21][22][23][24] . Because of the conflicting literature data, there is currently no consensus on tracheotomy as either a VAP-protective or VAP-causative factor 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The decision of perspective from which the analysis should be conducted, is an important consideration in pharmacoeconomic analysis. At present the pharmacoeconomic evaluation is valuable in individual patient treatment, total cost of care, resource allocation, and effective formulary management [29][30][31].…”
Section: Economic Features Of Vapmentioning
confidence: 99%
“…5,7 Outros estudos indicaram que a manutenção do paciente em prótese ventilatória de sete a doze dias eleva a suscetibilidade para o desenvolvimento de PAV, principalmente aqueles que se encontram traqueostomizados. [9][10][11] Assim, o tratamento intensivo por si só mostra-se um risco. E a probabilidade aumenta quando há a necessidade de transporte, que gera manuseio excessivo do paciente podendo levar à instabilidade do tubo orotraqueal ou da cânula de traqueostomia.…”
Section: Riscos Ligados Aos Procedimentos Em Terapia Intensivaunclassified